Development of Student Worksheets on Spatial Structure Material Based on Candi Penataran to Support Student Learning Outcomes - Anisah Salsabila; Asfira Zakiatun Nisa; Erni Anggraini; Marhayati Marhayati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study aimed to develop Student Worksheets (LKPD) based on Space Building Materials with a foundation in Penataran Temple to support student learning outcomes. The research also aimed to assess the validity of the LKPD and measure the improvement of student learning outcomes after using the LKPD. The research followed the development model proposed by Richey and Klein, consisting of three stages: planning, production, and evaluation. The planning stage included needs analysis, concept development, and LKPD development planning. An initial study was conducted to understand the challenges of teaching geometry to junior high school students, and strategies were designed to improve learning outcomes. Additionally, the planning stage involved observing Penataran Temple for concept development. The production stage involved creating and developing LKPD based on the concepts and objectives developed in the planning stage. LKPDs were developed with a focus on the concepts of Penataran Temple and Flat Side Spaces. The results of the pre-test and post-test analysis showed a significant increase in the average student score. The average pre-test score was 29.86, while the average post-test score was 64.93. The results also indicated an increase in the number of students who achieved the minimum passing score (KKM) in various schools with varying KKM standards. In a broader sense, the use of Penataran Temple-based flat-sided space building LKPD demonstrated a positive impact on students' understanding of space building and local culture, as well as improving their mathematical understanding and appreciation of culture.